PENGARUH KEBIJAKAN UTANG, KEPEMILIKAN INSTITUSIONALDAN MANAJEMEN LABA TERHADAP NILAI PERUSAHAAN - AJI P, SENO (Jurnal Akuntansi AKUNESA, 2017)
This study aims to determine the effect of debt policy, institusional ownership and earnings management on firm value. This research use quantitative method. The study’s population is all of firms registered in Bursa Efek Indonesia.This sample use 297 firms which selected using simple random sampling method and stratified sampling. Data was analyzed using multiple linear regression. The result study shows that debt policy does not affect firm value because debt is only one of many financial resources option for firm. Institutional ownership does not affect firm value because institutional ownership can’t reduce agency conflict between shareholder and management. Earnings management does not affect firm value because investors have been anticipating earnings management conducted by firm. Keywords : Debt Policy, Institusional Ownership, Earnings Management, Firm Value